An exploratory study for the psychological profile of a Civil Military Coordination Officer as a selection tool for training - Lloyd, Gary (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MComm (Industrial Psychology))--University of Stellenbosch, 2008.